2011
DOI: 10.1007/s12603-011-0340-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the association between muscle quality, inflammatory markers, and cognitive decline

Abstract: Objective Aspects of frailty such as sarcopenia and dementia are associated with a proinflammatory state; however, little research has examined the concurrence of these pathologies. This study examined sex-specific differences in the relationship between low muscle quality and impaired cognitive functioning, while considering the role of inflammatory markers. Design The nationally representative sample was drawn from a cross-sectional study. Participants Four hundred forty-five females and four hundred twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…Importantly, self-reported disability seems to correlate well with performance, with females testing as more disabled than males on performance measures (Merrill et al, 1997). Sex differences in biological factors, such as inflammatory cytokines, sarcopenia, abdominal adiposity and cognitive impairment, are emerging in the literature and probably underpin sex differences in co-morbidity and disability (Canon and Crimmins, 2011;Hubbard et al, 2010).…”
Section: Accepted M Manuscriptmentioning
confidence: 98%
“…Importantly, self-reported disability seems to correlate well with performance, with females testing as more disabled than males on performance measures (Merrill et al, 1997). Sex differences in biological factors, such as inflammatory cytokines, sarcopenia, abdominal adiposity and cognitive impairment, are emerging in the literature and probably underpin sex differences in co-morbidity and disability (Canon and Crimmins, 2011;Hubbard et al, 2010).…”
Section: Accepted M Manuscriptmentioning
confidence: 98%
“…Some research suggests that this relationship is stronger in women. For example, high inflammation was associated with poor cognitive performance in women but not men (Canon and Crimmins, 2011; Trollor et al, 2011). Similarly, another study found a correlation between high inflammation and mild cognitive impairment only in women (Trollor et al, 2010).…”
Section: Mechanisms Underlying Sex Differences In Obesity and Alzhmentioning
confidence: 99%
“…When stratified by gender, previous studies analyzing the distribution of elevated CRP (>3 mg/L), or the relationship between PA and CRP, have produced mixed results (4, 7, 17, 21, 23, 25). In a study of older adults conducted by Canon et al (7), analysis revealed that elevated levels of CRP mediated the relationship between cognitive function and muscle quality in females but not males.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have also shown that protocols utilizing MSA are effective in decreasing circulating levels of CRP (13, 20, 32). However, there are few gender-stratified studies analyzing the distribution of elevated CRP (>3 mg/L), or the relationship between PA and CRP, and the limited current literature has revealed mixed results (4, 7, 17, 21, 23, 25). The purpose of this study is to examine the associations between self-reported MSA and CRP in adult participants of the National Health and Nutrition Examination Survey (NHANES) when stratified by gender.…”
Section: Introductionmentioning
confidence: 99%